Empowering MSMEs: The Impact Of Financial Literacy And Inclusion : Systematic Literature Review - Amelia Setyawati; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (Pusat Riset dan Inovasi Nasional, 2023)
Micro, Small and Medium Enterprises (MSMEs) play a crucial role in the global economy by making a significant contribution to economic growth, job creation and increasing social inclusion. However, many MSMEs face challenges in optimizing their potential due to limited resources and access to financial services. Financial literacy among MSME players can be a fundamental pillar in forming smart and sustainable financial decisions. Financial inclusion provides wider access to financial services, such as banking and insurance, for MSMEs. With strong financial inclusion, MSMEs can overcome financial obstacles and take more measured risks, encourage innovation and stimulate local economic growth. The method used in this research is Systematic Literature Review (SLR) by collecting and analyzing journals related to keywords. Based on the literature study conducted, it was found that the importance of increasing financial literacy is the main key in helping Micro, Small and Medium Enterprises (MSMEs) overcome financial challenges and increase the effectiveness of business decision making. The need for more targeted financial education programs for MSME owners was also highlighted. In addition, supporting financial inclusion by providing wider and easier access to financial services can be a driver of MSME growth. Steps such as simplifying the credit process and integrating digital payment services are considered vital. Research also shows that there is a strong synergy between financial literacy and inclusion, where better financial literacy prepares MSMEs to utilize financial services, while effective financial inclusion facilitates their access to such services. Despite these developments, research highlights gaps in access to education and financial technology, emphasizing the need for more inclusive and holistic efforts to support MSME growth.